Review Article : The Effect of Quercetin Compounds on Type II Diabetes Mellitus - Wahyu Udayani, Ni Nyoman; Ni Putu Lilis Adnyani (International Journal of Educational and Life Sciences, 2024)
The immune system of the body targets the insulin-producing pancreatic cells, which results in diabetes mellitus. Synthesized antidiabetic drugs cause side effects of liver and kidney damage. Quercetin are known to have the same mechanism as synthetic antidiabetic drugs, so it can be an alternative treatment for diabetes. This article is a review with a literature search using PubMed, MDPI and Google Scholar. Quercetin activate AMPK which affects the decrease in blood glucose levels, protect cell damage due to free radicals so as to prevent a decrease in insulin levels and repair tissue damage due to hyperglycemia. Quercetin plays a role in reducing the risk of Type II DM complications. Quercetin compounds affect Type II Diabetes Mellitus with various mechanisms.